2008
DOI: 10.1016/j.cgh.2008.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Colorectal Adenomas in Younger Adults: An Epidemiologic Necropsy Study

Abstract: Background and Aims-The colorectal adenoma is the precursor lesion in virtually all colorectal cancers. Occurrence of colorectal adenomas has been studied in older adults but analysis in younger adults is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
40
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 20 publications
10
40
1
5
Order By: Relevance
“…We suggest that the reported left-to-right shift of colonic adenomas 19,20 is partly due to recent improvements in the detection of right colonic adenomas. This is supported by results from autopsy studies, some of them from the 1980s, which demonstrate an excess of adenomas in the right colon, 23,24,26,27 some of which presumably were missed by colonoscopy in past decades. Factors which may have contributed to the high detection rate of proximal adenomas in our study are: The excellent preparation for colonoscopy and the high coecal intubation rate.…”
Section: Discussionsupporting
confidence: 60%
“…We suggest that the reported left-to-right shift of colonic adenomas 19,20 is partly due to recent improvements in the detection of right colonic adenomas. This is supported by results from autopsy studies, some of them from the 1980s, which demonstrate an excess of adenomas in the right colon, 23,24,26,27 some of which presumably were missed by colonoscopy in past decades. Factors which may have contributed to the high detection rate of proximal adenomas in our study are: The excellent preparation for colonoscopy and the high coecal intubation rate.…”
Section: Discussionsupporting
confidence: 60%
“…Colorectal polyps are most commonly located in the rectosigmoid region and exhibit a decreasing incidence towards the cecum (Pendergrass et al, 2008). In their study in a series of 914 cases, Eminler et al (2011) reported that the adenomas were localized in the rectosigmoid region at a rate of 47.…”
Section: Discussionmentioning
confidence: 97%
“…In asymptomatic people, the prevalence of colorectal adenomas is about 25% to 30% at age 50 (21)(22)(23). Prevalence of colorectal adenomas increases with age, especially over the age of 50 (24). It has been discovered in autopsies that the prevalence of colorectal adenomas was 50% at age 70 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of colorectal adenomas increases with age, especially over the age of 50 (24). It has been discovered in autopsies that the prevalence of colorectal adenomas was 50% at age 70 (24). Most polyps are located in the left colon (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation